Exposures to climate change's physical risks in Chile - Magdalena Cortina; Carlos Madeira (Latin American Journal of Central Banking (LAJCB), 2023)
We estimate real estate's exposure in Chile to five weather risks, including labor productivity loss due to heat, fires, floods, drought coastal deterioration as measured by the Chilean Climatic Risk Atlas (ARCLIM) and Climate Impact Explorer (CIE) sources. According to our joint ARCLIM-CIE indicator, we measure risk exposure for the appraisal value of all properties of 39% for Chile and 51%, 36%, 36% and 27% for the Central, North, Metropolitan and South macrozones, respectively. Flooding is the greatest risk for Chile, followed by drought. We find that the CIE source underestimates the climate exposures in Chile relative to the ARCLIM measures, particularly for the flooding and drought risks.
Keywords: O44; O54; Q51; Q59; R11; 330; Exposures to climate change; Global warming; Latin america; Physical risks from climate change; Real estate